(untitled) (Journal of Pharma Insights and Research, 2024)
Probiotics—whose name comes from the Greek word meaning "for life"—are live bacteria that have been shown to have health advantages. An overview of the crucial function probiotics play in preserving the microbial balance in the human body, especially in the gastrointestinal system, is given in this review. Probiotics are important for digestion, immune system activation, and pathogen resistance since the gut contains about 500 distinct bacteria species. They support a number of metabolic processes, including as the digestion of carbohydrates, and the emergence of metabolic diseases such colon cancer and inflammatory bowel disease (IBD) has been linked to their dysbiosis. Prebiotics, postbiotics, and probiotics constitute a rapidly developing field of study with enormous promise for the creation of pharmaceuticals. The review highlights their diverse applications in treating gastrointestinal and non-gastrointestinal disorders, including diarrhea, inflammatory responses, and viral infections. Despite their promising benefits, probiotics carry risks, particularly in vulnerable populations, where they may lead to systemic infections. Understanding their mechanisms of action and potential adverse effects is crucial for their safe and effective utilization. Over the past two decades, probiotics have gained recognition as medical treatments, with the food industry spearheading their incorporation into various products. The World Health Organization acknowledges probiotics as a cost-effective and safe intervention against microbial illnesses, positioning them as a secondary immune system. As research in this field advances, probiotics hold significant promise for revolutionizing healthcare practices and offering novel therapeutic strategies for a wide spectrum of diseases